Vibration control of vortex-induced vibrations of a bridge deck by a single-side pounding tuned mass damper. (15th October 2018) - Wang, Wenxi; Wang, Xiuyong; Hua, Xugang; Song, Gangbing; Chen, Zhengqing
Highlights: A nonlinear impact force model is used to represent the impact behaviors of VE materials in SS-PTMD. The optimal design of SS-PTMD for SDOF structure subjected to harmonic excitation is carried out. The optimized SS-PTMD is used to control the vortex-induced vibrations of a bridge deck. The classical wake oscillator model is used to explore the control performance of the SS-PTMD. Abstract: This paper proposes a new method to mitigate vortex-induced vibrations (VIVs) of a bridge deck using a single-side pounding tuned mass damper (SS-PTMD). The SS-PTMD is a passive control device and comprises an undamped tuned mass with a pounding boundary covered with viscoelastic (VE) materials layer. A nonlinear force model for describing impact behavior of VE materials is used to simulate the response of a single degree of freedom (SDOF) system controlled by a SS-PTMD. The free pounding experiments are performed to determine the model parameters of impact force and validate the simulation method. The optimal design of SS-PTMD for SDOF system subjected to sinusoidal excitation is carried out by numerical optimization, and the optimized SS-PTMD is applied to control the vertical VIVs of a bridge deck. The control performance is experimentally examined by elastically mounted section model tests in wind tunnel. In addition, the classical wake oscillator model is used to predict the behavior of the coupled fluid-structure system under VIV and explore the control performance of the SS-PTMD. The experimental results show that the maximum response of the bridge deck model was reduced by 94% when a SS-PTMD with mass ratio of 2% was applied. It is also shown that nonlinearity in vortex shedding forces has little influence on control performance of SS-PTMD optimized under sinusoidal excitation.